Strižna odpornost nearmiranih zidov - Tomaževič, Miha (Gradbeni vestnik, 2009)
Shear failure, characterized by the occurrence of diagonally oriented cracks, is a typical failure mode of unreinforced and confined masonry walls subjected to in-plane seismic loads. Although other mechanisms are also possible, seismic resistance of a regular masonry structure depends predominantly on the shear resistance of structural walls. The results of cyclic lateral resistance tests of different types of unreinforced walls with two height/length aspect ratios and tested at different compressive stress/compressive strength ratios, have been used to compare the experimentally obtained resistance values with the results of calculations. Ithas been shown that typical equations used for the calculation of the shear resistance of walls, which are based on either shear friction or diagonal tension failure mechanisms, do not have general validity, because they reflect the type of the shear failure, for which they had been developed. Whereas good correlation between experimental results and calculations has been obtained if the equations based on the diagonal tension failure mechanism have been used, the calculations based on the shear friction failure mechanism overestimated the actual resistance of the tested walls.
Keywords: modeliranje; preiskava materiala; strižna trdnost; votlaki; zid